Descriptive Writing Ability of Elementary Students Using Picture Media: A Qualitative Analysis: Kemahiran Menulis Deskriptif Siswa Sekolah Dasar Menggunakan Media Gambar: Analisis Kualitatif - Dinda Destari; Nurun Nisa; Nurainun Ayu Fathanah (ELOQUENCE : Journal of Foreign Language, 2025)
Background: According to the Program for International Student Assessment (PISA) 2018, Indonesia was 74th out of 79 countries in reading literacy. This PISA result shows that Indonesian students' reading and writing skills are much worse than those of students in Thailand, Malaysia, and other countries in the Asia-Pacific region. Writing ability is one of the most important parts of being literate. Purpose: This study investigates the vocabulary utilization of elementary school students in composing descriptive paragraphs through the use of visual media. The study aims to ascertain the descriptive paragraph writing proficiency of elementary students utilizing pictorial media, to delineate the disparities in the quantity and diversity of vocabulary employed by the students, and to examine the factors contributing to challenges in composing descriptive paragraphs. Method: This study utilizes a qualitative descriptive methodology. The study's population comprises students from SDN 07 Kota Jantho, located in Aceh Besar District. The sample was chosen using purposive sampling, which meant that 30 students from grades IV, V, and VI were chosen. The research instrument employed consisted of colored images aimed at assessing the students' capacity to compose descriptive paragraphs. Results and Discussion: The study's findings reveal disparities in writing proficiency among students at different grade levels, predominantly characterized by the use of elementary vocabulary and straightforward sentence structures. The number of sentences produced by Grade VI students is consistently higher compared to those in Grades IV and V. This reflects a greater maturity in expressing ideas and maintaining topic continuity throughout a paragraph. Conversely, various factors were recognized as contributors to writing challenges, such as insufficient ideas, restricted vocabulary, diminished interest, inadequate comprehension of paragraph structure and visual content, and a deficiency in self-confidence. Conclusions and Implications: This study also contributes to mapping the basic writing abilities of elementary school students in Aceh Besar, which have previously been limited in empirical research. These findings are expected to serve as a reference for teachers, policymakers, and other researchers in designing more contextual literacy programs based on students’ needs.